PLANNING AND MANAGEMENT: A REASSESMENT OF THE POLICY DEVELOPMENT FOR TOURISM ACTIVITIES IN THE STATE OF CEARÁ / BRAZIL - Muniz, Ana Cristina Fernandes; Oliveira, Huáscar Pinto Vidal de; Oliveira, Vládia Pinto Vidal de (Tourism & Management Studies, 2013)
The tourism industry has emerged with modern features, which dominates a large dependency relationship with the environment through the use of natural resources. Currently sharp features of consumption and individualism, mass consumption contributed decisively to its expansion and in this context, it is necessary to effective management and planned for the sector. From this perspective, this text makes a reassessment of the management policies and planning for economic development in the territory of Ceara, through of the proposed planning and management in the subsidized Public Policy Planning and Development, which boosted tourism in the 1990s, the state of Ceará.